A Reexamination of Firm Size, Book-To-Market, and Earnings Price in the Cross-Section of Expected Stock Returns - Kim, Dongcheol (Journal of Financial and Quantitative Analysis, 1997)
Dongcheol Kim, A Reexamination of Firm Size, Book-To-Market, and Earnings Price in the Cross-Section of Expected Stock Returns, The Journal of Financial and Quantitative Analysis, Vol. 32, No. 4 (Dec., 1997), pp. 463-489